PENGARUH TEAMS GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR MATEMATIKA KPK DAN FPB DI SEKOLAH DASAR - Sopiani; Siti Halidjah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the TGT model on the learning outcomes of fourth-grade students at SDN 06 Pontianak Timur regarding the topics of GCD and LCM. The research design used was quantitative research with a pre-experimental approach employing a one-group pretest-posttest design. The population and sample consisted of 30 fourth-grade students, with the entire population serving as the sample (saturation sampling). Data were collected using a multiple-choice test instrument consisting of 20 questions. From the results of the hypothesis test analysis, the results of the paired sample test with the final data obtained from the pretest and posttest scores were 11.804 with df = 29 and a significance level of 0.05, yielding a p-value of 0.000. Thus, 0.000 < 0.050, which means that H1 is accepted and H0 is rejected, indicating that the model has an effect.